63 776
Assignments Done
99,3%
Successfully Done
In August 2018

Answer to Question #11887 in Algebra for Sadia

Question #11887
if x=(p+q)/(p-q), then x-1=?
Expert's answer
x-1=(p+q)/(p-q)-1=(p+q-(p-q))/(p-q)=(p+q-p+q)/(p-q)=(q+q)/(p-q)=2q/(p-q)

Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be first!

Leave a comment

Ask Your question

Submit
Privacy policy Terms and Conditions